Multi-scale analysis of mechanical properties and damage behavior of polypropylene composite (GF50-PP) plate at room and cryogenic temperatures. (15th December 2021) - Shirinbayan, Mohammadali; Rezaei-khamseh, Mojdeh; Nikooharf, Mohammad Hossein; Tcharkhtchi, Abbas; Fitoussi, Joseph
Graphical abstract: Abstract: In this paper, glass fiber-reinforced polypropylene (GF50-PP) composite composed of long fibers was prepared by the thermo-compression process for the very first time. This composite presents high mechanical strength and is used in infrastructures, which demand resistance against severe conditions. Mechanical strength and multi-scale damage analysis of GF50-PP composite at ambient and cryogenic temperatures have been investigated in this study using a special sampling procedure according to the microscopy observation, X-ray microtomography, ultrasonic measurement, and pyrolysis. The results demonstrated the exceptional behavior of the GF50-PP at the cryogenic temperature of −70 °C mainly due to the employment of a novel processing method (thermo-compression) for composites with long fibers, which have been previously prepared by traditional injection molding process. Tensile results presented no difference in failure strain at 20 °C and −70 °C and the fatigue lifetime for different fiber orientations was similar in 3-points bending fatigue tests for different orientations of fibers or in samples taken from different regions of the composite plate, indicating the efficinecy of this processing method. Moreover, the results of damage analysis through monotonic loading presented that by decreasing the temperature from 20 °C to −70 °C, the plasticity threshold didn't change notably. Overall, the proposed preparation method provided outstanding uniformity and excellent mechanical properties in GF50-PP composite even at temperatures as low as −70 °C, which has not been investigated at this cryogenic temperature before.